PENGARUH PEMBERIAN POC BATANG PISANG TERHADAP PERTUMBUHAN BIBIT KOPI ROBUSTA (Coffea robusta L.) - monly, veronika; Nurhayati, Nurhayati; Rosmalinda, Rosmalinda (Politeknik Negeri Ketapang, 2023)
Coffee (Coffea sp.) is one of the leading plantation crop commodities in Indonesia, because Indonesia is a country with the third largest coffee production in the world besides Brazil and Vietnam. The importance of coffee plants in the Indonesian economy makes the demand for coffee plants increase. This study aims to determine the effect of giving banana stem POC on the growth of coffee seedlings. This study used a completely randomized design (CRD) with 5 treatments, namely (P0) = POC banana stem 0 ml L-1 water, (P1) = POC banana stem 160 ml L-1 water, (P2) = POC banana stem 200 ml L-1 water (P3) = POC banana stems 240 ml L-1 water, (P4) = POC banana stems 280 ml L-1 water. Each treatment was repeated 3 times, so there were 75 experimental units. POC banana stem dose of 280 ml L-1 water is the best dose that can increase the vegetative growth of coffee plants on the parameters of plant height, stem diameter, number of leaves, root length and plant dry weight.